OP0157-HPR "This Feeling!": Can a New Ipad App Help Children with Juvenile Idiopathic Arthritis Communicate their Pain Experiences? Feasibility, Usability and Acceptability. (9th June 2015) - Tapping, P.; Rashid, A.; Thomson, W.; Ghio, D.; Cordingley, L.; Calam, R.; Jimmieson, P.; Chieng, A.
Abstract : Background: Pain is the most common symptom of Juvenile Idiopathic Arthritis (JIA), and it is known to cause significant distress for young people. Despite advances in treatment, pain is often still poorly managed. Multidimensional approaches are needed to help children with JIA communicate better about their pain experiences with healthcare professionals and parents. A new interactive iPad application called "This Feeling" has been developed in collaboration with children and healthcare professionals to aid communication about pain in children with JIA. "This Feeling" enables young people to describe the pain type, intensity, location, spread and emotional impact at a given time, by using an interactive manikin, adjustable pain icons, facial expressions, drawing tools and free text description. Objectives: The aim of this research was to explore the acceptability, usability and feasibility of "This Feeling" to communicate pain experiences in children with JIA by comparing the tool with self-report measures commonly used in clinic: the Visual Analogue Scale (VAS) and The Faces Pain Scale, Revised (FPS-R). Methods: Young people aged between 5 and 16 and consenting caregivers were recruited from a city centre hospital in England, which was part of the Childhood Arthritis Prospective Study (CAPS), a large scale prospective inception cohort. A cross-sectional design using mixed methods compared self-report measures (the VAS and FPS-R) with "This Feeling". The measures were administered in random order to young people attending an outpatients' clinic. Semi-structured interviews were used to elicit views on completing "This Feeling" compared with standardised measures. Results: The sample consisted of 43 young people and their caregivers. All participants were able to use "This Feeling" to describe their pain experiences (average completion time 8 minutes). The majority (95%) preferred using "This Feeling" over the VAS and FPS-R, and found it easier and more interesting to communicate their pain experiences. Participants suggested modifications including a zoom function as well as an icon to indicate "No Pain". Usability feedback indicated that the shading function interfered with pain icons which young people had already placed on the manikin. Parents praised "This Feeling" for capturing the multidimensional nature of pain in an easy and "child friendly" nature, over the conventional pain measures. Conclusions: "This Feeling" appears to be a feasible, usable and acceptable system for communicating the multidimensional nature of pain in children with JIA. Future modifications will be addressed. Plans are being made to validate the different components of "This Feeling", specifically, the facial expressions, the body map and pain severity and intensity scales to develop this further as a pain assessment tool. Acknowledgements: The Childhood Arthritis Prospective Study Disclosure of Interest: None declared